(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the process of modelling combat operations and to organize the fight against sabotage-intelligence groups, estimates of their combat capability indicators have been derived and suggested.